The molecular basis of cancer metastasis: multi-step metastasis process and anti-metastasis therapeutic development - Yang, Jing (Henry Stewart Talks, 2023)
Molecular regulation of EMT, Adherens junction, E-cadherins, Epithelial-Mesenchymal Plasticity, Metastasis dormancy, Metastasis organ tropism, Targeting tumor metastasis